Design typological analysis for urban water management: why quantification is needed and how it can be done? / Mojtaba Moravej and Paola Leardini - Moravej, Mojtaba; Leardini, Paola (2022)
This paper describes urban design typological analysis for water management, an emerging multidisciplinary design method involving urban planning, architecture, urban water engineering, hydrology, and sustainability fields. The challenge in multidisciplinary design is that it often results in ‘too many’ options, therefore, consistently and systematically comparing and evaluating interdisciplinary alternatives is difficult. We addressed this gap by reviewing evaluation frameworks, water performance quantifications methods and water indicators to identify their strength and weaknesses for design typological analysis. We first reviewed urban water management goals and conducted a review-of-reviews to identify suitable methods and indicators that can link design typological analysis to urban water management objectives. The results identified analysis was most often underpinned by urban water metabolism, economic evaluation, life cycle assessment, and water neutrality. Their function for exploring trade-offs, ranking options, and informing the decision-making process were discussed and a generalised synthesis of principles for design typological analysis is presented. The literature review also identified three main categories of models suitable for water performance quantifications, namely urban drainage, urban water mass balance, and integrated urban water system models. We suggest that urban water mass balance is used for design typological analysis due to its flexibility regarding the issue of scale (site, precinct, city, etc.) and comprehensive accounting of urban water flows. The results have great implications for sustainable urban water management in relation to the risks associated with pluvial flooding and water insecurity. They also highlight the underutilised role of architects and urban planners to address urban water issues.